Treating Anemia in the Preanesthesia Assessment Clinic: Results of a Retrospective Evaluation. (November 2018) - Ellermann, Ines; Bueckmann, Andreas; Eveslage, Maria; Buddendick, Hubert; Latal, Tobias; Niehoff, Dennys; Geissler, R. Georg; Hempel, Georg; Kerkhoff, Andrea; Berdel, Wolfgang E.; Roeder, Norbert; Van Aken, Hugo K.; et al.
Abstract : BACKGROUND: Perioperative anemia is challenging during hospital stay because anemia and red blood cell (RBC) transfusions are associated with an increased morbidity and mortality. With the implementation of patient blood management (PBM), a preanesthesia assessment clinic to screen and treat anemia before elective surgery was institutionalized at Muenster University Hospital, Germany. The main objective of this study was to evaluate the association between treating preoperative anemic patients with intravenous iron (IVI) and (primarily) presurgical hemoglobin levels and (secondarily) use of RBCs and mortality. METHODS: Between April 1, 2014, and July 4, 2016, patients scheduled for elective surgery with a risk for RBC transfusions >10% in 2013 were screened for preoperative anemia and, if indicated, treated with IVI. Patients' data, time span between visit in the anesthesia/PBM clinic and surgery, demographic data, type of surgery, the difference of hemoglobin levels between visit and surgery, RBC transfusion, infectious-related International Classification of Disease codes during hospital stay, and 1-year survival were determined retrospectively by screening electronic data files. In addition, patients were interviewed about adverse events, health-related events, and infections via telephone 30, 90, and 365 days after visiting the anesthesia/PBM clinic. RESULTS: A total of 1101 patients were seen in the anesthesia/PBM clinic between days −28 and −1 (median [Q1–Q3], −3 days [−1, −9 days]) before elective surgery. Approximately 29% of patients presented with anemia, 46.8% of these anemic patients were treated with ferric carboxymaltose (500–1000 mg). In the primary analysis, hemoglobin levels at median were associated with a reduction between the visit in the anesthesia/PBM clinic and the surgery in all nonanemic patients on beginning of medical treatment (nonanemic patients at median −2.8 g/dL [−4, −0.9 g/dL], while anemic patients without IVI presented with median differences of −0.8 g/dL [−2, 0 g/dL] and anemic patients with IVI of 0 g/dL [−1.0, 0.5 g/dL]). Hemoglobin levels raised best at substitution 22–28 days before surgery (0.95 g/dL [−0.35, 1.18 g/dL]). Due to the selection criteria, transfusion rates were high in the cohort. Overall, there was no association between IVI treatment and the use of RBC transfusions (odds ratio for use of RBCs in anemic patients, no IVI versus IVI: 1.14; 95% confidence interval, 0.72–1.82). Patients treated with or without IVI presented a comparable range of International Classification of Disease codes related to infections. Telephone interviews indicated similar adverse events, health-related events, and infections. Cox regression analysis showed an association between anemia and reduced survival, regardless of IVI. CONCLUSIONS: An anemia clinic within the preanesthesia assessment clinic is a feasible and effective approach to treat preoperative anemia. The IVI supplementation was safe but was associated with decreased RBC transfusions in gynecology/obstetric patients only. The conclusions from this retrospective analysis have to be tested in prospective, controlled trials.